The Structural Model of Identity Instability Based on Object Relations and Childhood Trauma with the Mediating Role of Mental Pain - Malekzadeh, Fatemeh Zhinous; Mohammadipour, Mohammad; Jajarmi, Mahmoud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to examine a structural model in which adverse childhood experiences and relational disturbances predict self-injurious behaviors through the mediating roles of identity diffusion and psychological pain in adolescents. Methods and Materials: The study employed a descriptive–correlational design using structural equation modeling. Participants were adolescents who completed standardized self-report measures assessing adverse childhood experiences, relational disturbances, identity diffusion, psychological pain, and self-injurious behaviors. Data were analyzed using confirmatory factor analysis to evaluate the measurement model, followed by structural equation modeling to test direct and indirect pathways among variables. Model fit was assessed using multiple goodness-of-fit indices, and indirect effects were examined to determine the mediating roles of identity diffusion and psychological pain. Findings: The results indicated that adverse childhood experiences and relational disturbances had significant positive effects on identity diffusion and psychological pain. Identity diffusion was a significant predictor of psychological pain, and psychological pain showed a strong direct effect on self-injurious behaviors. Indirect pathway analyses revealed that the effects of early relational adversity on self-injury were partially mediated by identity diffusion and psychological pain. The overall structural model demonstrated acceptable fit indices and substantial explanatory power for self-injurious behaviors. Conclusion: The findings support a developmental–relational model of adolescent self-injury in which early adversity and relational disruptions contribute to identity fragmentation and psychological pain, thereby increasing vulnerability to self-injurious behaviors, highlighting the importance of addressing internal suffering and identity processes in prevention and intervention efforts.